Animal Coloration in the Anthropocene - Koneru, Manisha; Caro, Tim (Frontiers in Ecology and Evolution, 2022)
Natural habitats are increasingly affected by anthropogenic environmental changes from chemical and light pollution to climate change and habitat destruction. Organisms inhabiting these habitats are faced with novel disturbances that alter their modes of signalling. Coloration is one such sensory modality whose production, perception and function is being affected by human induced disturbances. Animals that acquire pigment derivatives through diet are adversely impacted by the introduction of chemical pollutants into their environments as well as by the general loss of habitat due to urbanization or logging leading to declines in pigment sources. Those species that do manage to produce colour based signals and displays face may disruptions in their signalling medium in the form of light pollution and turbidity. Furthermore, forest fragmentation and the resulting breaks in canopy cover can expose conspicuously coloured animals to predators due to the influx of light into previously dark environments. Global climate warming has been decreasing snow cover in arctic regions, causing birds and mammals that undergo seasonal moults to appear conspicuous against a snowless background. Ectotherms that rely on colour for thermoregulation are facing evolutionary shifts in their colour phenotypes due to changing selective pressures. Rapid changes in habitat type through severe fire events or coral bleaching present animals that have adapted to match their backgrounds with new stimuli to respond to. Through this review, we aim to describe the wide-ranging impacts of anthropogenic environmental changes on visual ecology and suggest directions for the use of coloration as a valuable indicator of ecological change and as a tool for conservation.